A Robust Audio Watermarking Algorithm Based on SVD-DWT - Zhao, Huan; Wang, Fei; Chen, Zuo; Liu, Jun (Elektronika ir Elektrotechnika, 2014)
In this paper, we proposed a novel blind audio watermarking algorithm, which combined Singular Value Decomposition(SVD) with Discrete Wavelet Transform(DWT). In our algorithm, We first partition the rearranged audio signal into blocks, then generate the vector by selecting the biggest singular values after performing SVD on these blocks. Finally we embed the watermark into the approximate components obtained from the DWT decomposition of the vector by means of quantization process. Experimental results showed that our algorithm has good robustness against the common audio signals processing operations. Compared with earlier schemes based on SVD, the proposed scheme has satisfying imperceptibility and improved payload. DOI: http://dx.doi.org/10.5755/j01.eee.20.1.3948